Meeting the needs of older people living in Australian residential aged care: A new conceptual model. (9th April 2020) - Ibrahim, Joseph E; Fetherstonhaugh, Deirdre; Rayner, Jo‐Anne; McAuliffe, Linda; Jain, Briony; Bauer, Michael
Abstract: Objective: To report on the conceptualisation of a model for residential aged care in Australia. Methods: Three‐stage approach involving initial model conceptualisation; extensive consultation with stakeholders to test and develop the model for feasibility and acceptability; and examination of whether the model addresses circumstances that arise in scenarios of organisational failure. Results: A model consisting of five domains relevant to the experience of older adults living in residential aged care—health care; social inclusion; rights; personal care and re‐ablement; and dementia management. Conclusions: This proposed model of residential aged care takes as its purpose the provision of person‐centred care to older people with complex health issues, requiring end‐of‐life care, and/or living with dementia. This includes supporting dignity of risk and quality of life and enabling older adults to thrive.